Implementation of Tahfidz Learning in Developing Religious Character at SMAS Wahid Hasyim Mojogeneng Jatirejo Mojokerto - Wardani, Handini Tria; Ma’arif, M. Anas (Yayasan Pendidikan Bustanul Ulum Mojokerto, 2024)
Islamic education is the main foundation in the character-building of students in SMAS Wahid Hasyim. One important aspect of Islamic education is tahfidz Al-Qur'an, which aims to memorize the Qur'an and integrate Islamic values ​​into students' lives. This study aimed to explore the implementation of tahfidz Al-Qur'an learning in developing students' religious character in SMAS Wahid Hasyim. This research method uses a qualitative approach with a case study research type. Data were collected through observation, interviews, and document analysis. The sources of this study were the Principal, Deputy Curriculum, Homeroom Teachers, and Tahfidz Teachers at SMAS Wahid Hasyim. The results of the study showed that the implementation of tahfidz Al-Qur'an learning had a significant impact on the development of students' character, who were initially still too lazy to worship but after they understood the contents of the Qur'an they were finally able to make the best use of their time when they were free at school. Likewise, before understanding the contents of the Qur'an, their manners towards their teachers and parents were still lacking. Still, after understanding the contents of the Qur'an, they became more respectful towards their teachers and parents. In conclusion, implementing tahfidz Al-Qur'an learning at SMAS Wahid Hasyim has an important role in developing students' religious character. Therefore, it is recommended that tahfidz Al-Qur'an learning continue to be improved and supported by various innovative learning strategies and methods to prove students' success in understanding and practicing the teachings of the Qur'an in their daily lives.